Time Management Strategies for Nurse Leaders: A Comprehensive Review - Almutairi, Dalal Mohammed Awad; Albathali, Ghazlan Maseer; Alanazi , Lama Wahab Munaykhir; Alakrah, Salha Hassan; Alenezi, Mmusad Khalaf; Alsharari, Adel Abdullah Funtul; Alshrari, Fahad Mohammed Eid; Alruwaili, Sarah Mukilf Nmr; Al Dosari, Rashid Mohammed Amer; Al-Saeed, Bushra Abdulrahman; Al Rashidi, Hanan Kalaf; Samily, Ahmad Khaled Ahmad; et al. (Journal of Ecohumanism, 2024)
Background: The COVID-19 pandemic has resulted in unprecedented challenges for healthcare systems worldwide, significantly impacting the well-being of nursing students and professionals. This review aims to explore the specific stressors faced by nursing students during the pandemic and the coping mechanisms they employed to navigate these challenges. Methods: A scoping review was conducted, analyzing literature from multiple databases, including CINAHL, MEDLINE, Google Scholar, and PubMed. The search focused on studies published during the pandemic that examined stressors and coping strategies among nursing students. Results: The review identified four primary stressors: difficulties associated with distance learning, increased academic workload, challenges during clinical training, and fears related to COVID-19 infection. Additionally, various coping strategies were highlighted, including information-seeking, maintaining optimism, and engaging in transference activities to alleviate stress. The findings underscored that nursing students faced heightened anxiety levels due to the abrupt transition to online education and the pressures of clinical responsibilities. Conclusion: The COVID-19 pandemic has intensified stressors for nursing students, necessitating effective coping strategies to ensure their academic success and mental well-being. Understanding these stressors and coping mechanisms is essential for developing targeted interventions to support nursing students in crisis situations